Analytical framework on climate projection and its illustration of risks to nutritional health in the Solomon Islands - Zina Bird; Viliamu Iese; Morgan Wairiu (Frontiers in Sustainable Food Systems)
The connection between agriculture and food security is well recognized, nonetheless, the long-term effects of climate change on the nutritional value of tropical produce in the Pacific are not well understood. Firstly, to understand the food and nutritional security in the Pacific, the study highlights a significant gap in existing food security frameworks between the impact of climate change, nutritional change in food crops and vegetables, and consumption. Emphasizing the need for more integrated approaches. Secondly, an analytical framework is proposed, built from systematic literature reviews, following a six-step: defining the research question, performing keyword-based searches, screening results, assessing full-text eligibility, extracting and synthesizing data, and reporting findings. Literature was sourced from academic databases, institutional repositories, and organizational websites, resulting in 73 relevant studies being included from platforms and databases such as PubMed, ScienceDirect, ProQuest, and others. This framework aims to connect climate projections with soil nutrients, crop and vegetable quality and nutrients, and dietary outcomes. Thirdly, the study stresses the importance of improving collaboration among governmental ministries and experts, as well as embracing technological innovations, to ensure effective nutrient flow from soil to crops and ultimately to consumers. It emphasizes the need to evaluate the potential nutritional consequences of climate change to safeguard nutritional security for affected populations. Finally, the framework is tailored to the Solomon Islands to inform policy recommendations that enhance food security and nutrition from the production to consumption phase. This approach highlights the interconnectedness of environmental sustainability, agricultural practices, and public health, advocating for a holistic strategy to tackle these pressing challenges.